A Stylistic Study of Joker’s Dialogue in the Dark Knight (2008): The Language of Villain - Syakira, Shofy Zahwa; Djuharie, Otong Setiawan; Saehu, Andang (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
This study explores the stylistic features found in the dialogue of the character Joker in The Dark Knight, directed by Christopher Nolan. As one of the most iconic villains in modern cinema, Joker is distinguished by his unconventional, provocative, and psychologically charged use of language. Through a stylistic approach, this research analyzes linguistic elements such as diction, sentence structure, figurative language, and repetition aiming to uncover how these features contribute to the construction of Joker’s identity as a villain. The study employs a qualitative descriptive method, with data drawn from selected excerpts of Joker’s dialogue. The analysis is guided by the stylistic framework of Geoffrey Leech and Mick Short. Ultimately, this research seeks to offer a deeper understanding of how language is used not only to shape character and ideology but also to evoke psychological impact within popular media narratives. Abstrak Penelitian ini bertujuan untuk menganalisis gaya bahasa (stylistic features) dalam dialog karakter Joker dalam film The Dark Knight karya Christopher Nolan. Joker merupakan tokoh antagonis yang ikonik, dengan cara berbicara yang tidak konvensional, provokatif, dan penuh dengan makna tersembunyi. Melalui pendekatan stilistika, penelitian ini mengeksplorasi unsur-unsur linguistik seperti diksi, struktur kalimat, majas, dan repetisi yang berperan dalam membentuk identitas Joker sebagai sosok villain. Metode penelitian yang digunakan adalah deskriptif kualitatif, dengan data berupa kutipan-kutipan dialog Joker yang dianalisis berdasarkan teori stilistika dari Geoffrey Leech dan Mick Short. Hasil yang diharapkan dari penelitian ini adalah pemahaman yang lebih mendalam tentang bagaimana bahasa digunakan sebagai sarana untuk membangun karakter, menyampaikan ideologi, serta menciptakan dampak psikologis dalam media populer.